Analysis and systematic verifications of a low-IF RF receiver targeting GNSS applications - Pramoda, Damle (2018)
Positioning methods built on the basis of Global Navigation Satellite System (GNSS) like GPS, GLONASS, Beidou and Galileo system find popular applications in tracking systems, automobile and air navigation, surveying, mapping and geographic information systems, archaeology, and pedestrian navigation systems (PNSs). Increasing number of radio frequency front-end chips integrated to a high degree are realized in the ground GNSS receivers to achieve the low power consumption and low cost demand. The processing of signals from each of the above satellite systems of GNSS is performed using the same receiver. A low-IF RF receiver used for such purpose has many key performance parameters such as overall RF receiver gain, RF front-end gain, ripple, filtering, noise figure, s-parameters, spurious response rejection, power supply rejection ratio, and the non-linearity parameters such as IIP2, IIP3, and P1dB compression point. This thesis work will discuss about the receiver architectures and constituent blocks followed by a description of receiver performance parameters along with the methods to simulate and verify them in Cadence Analog Design Environment.